2016
DOI: 10.3109/10826084.2015.1058823
|View full text |Cite
|
Sign up to set email alerts
|

Types and Characteristics of Childhood Sexual Abuse: How Do They Matter in HIV Sexual Risk Behaviors Among Women in Methadone Treatment in New York City?

Abstract: This study contributes to understanding of relationships between CSA and HIV sexual risk behaviors and key correlates associated with HIV sexual risk behaviors among women in methadone treatment. It also highlights the complexity of measuring CSA and its association with sexual risk behaviors and the importance of comprehensive approaches to HIV prevention that address psychological, relational, situational, and substance use experiences associated with sexual risk behaviors among this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
(104 reference statements)
1
7
0
Order By: Relevance
“…The findings from the current study are consistent with several prior studies demonstrating benefits of informal social support in relation to HIV risk behaviors among women (El-Bassel & Schilling, 1994;Engstrom et al, 2016;Nyamathi, Stein, & Swanson, 2000;Sobo, 1995). However, our findings also indicate that formal social support reflected in recent substance use treatment is associated with having a partner with increased HIV risk factors.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings from the current study are consistent with several prior studies demonstrating benefits of informal social support in relation to HIV risk behaviors among women (El-Bassel & Schilling, 1994;Engstrom et al, 2016;Nyamathi, Stein, & Swanson, 2000;Sobo, 1995). However, our findings also indicate that formal social support reflected in recent substance use treatment is associated with having a partner with increased HIV risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…It may be that substance use treatment provides an opportunity for women on probation and parole to meet partners who are also addressing substance use difficulties and experiencing multiple risks for HIV. Additionally, the finding that nearly 56% of the women in this study reported having partners with one or more HIV risks (a potentially conservative estimate in that our partner risk measure focused solely on four factors related to injection drug use, involvement with male intimate partners, incarceration, and timing of initial sexual activity) and connections between reliance on partners for basic needs and substance use resources and risks for HIV among women who use substances (Amaro & Hardy-Fanta, 1995;El-Bassel & Schilling, 1994;Engstrom, El-Bassel, & Gilbert, 2012;Engstrom et al, 2016) further support the value of relationshiporiented HIV prevention strategies. There is evidence that such intervention may be especially effective at reducing HIV risk behaviors among women with ongoing intimate partners (El-Bassel et al, 2010;Jones, Kashy, Villar-Loubet, Cook, & Weiss, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A number of risk factors have been associated with IPV that increase the likelihood of acquiring and transmitting HIV infections. These factors include forced sexual activity, accessory injuries to vagina or other body parts, microscopic lacerations and tears to the anal and buccal mucosa as well as nail injuries to skin and other sensitive areas thereby increasing viral contact to the raw wounds and increasing transmission rates (Gilbert et al, 2016). In addition, women experiencing IPV are often subjected to nonconsensual sexual activities without any open communication about risk factors such as promiscuity, extramarital affairs, or commercial sex worker contact .…”
Section: Summary and Limitationsmentioning
confidence: 99%